KEPUASAN KERJA MEMEDIASI PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA MARGA YUMNA ADVENTUR - Sadhana, I Putu Dharma; Satrya, I Gusti Bagus Honor (E-Jurnal Manajemen; Vol 9 No 7 (2020), 2020)
This research was conducted on the employees of PT. Marga Yumna Adventur. The purpose of this study was to determine the effect of job satisfaction as a mediating variable between the perceived organizational support and organizational citizenship behavior. The samples take were as many as 62 respondents. Data collection was carried out by distributing questionnaires. The analysis technique used is descriptive statistics, path analysis and sobel test. The results of the analysis show that perceived organizational support has a positive and significant effect on job satisfaction, this indicates that the more support is given by the management of PT. Marga Yumna Adventur, employee satisfaction will increase. Job satisfaction and perceived organizational support have a positive and significant effect on OCB, this means that the higher the level of satisfaction felt by employees and the more support given by the management of PT. Marga Yumna Adventur, the higher the OCB employees have. Job satisfaction has a positive and significant effect mediating the role of perceived organizational support for OCB, this means that more support is given by the management of PT. Marga Yumna Adventur, employee satisfaction will increase and then will result in better OCB behavior for employees. Keywords: perceived organizational support, job satisfaction, OCB